ANALISIS POMPA HYDRAULIC KILN TRHUSTER DAN PERAWATAN PADA ROTARY KILN PLANT 10 PT X - Sonjaya, Cecep; Rachmat, Asep (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
Abstract Hydraulics have been widely used, especially in the industrial world and have become a very important component because the hydraulic system can make machine work more economical. Many industrial processes use hydraulic systems to assist in the production process. One that uses a lot of hydraulic systems is the cement industry. PT Indocement Tunggal Prakarsa Tbk uses a hydraulic system in almost every component of its production. One of the production components that use it is the Rotary Kiln Kiln is a component that functions to burn cement raw materials and mix them by rotating continuously. Rotational movement that occurs can cause a shift in the kiln. To overcome this shift, there is one important component in the kiln circuit, namely the Hydraulic kiln thruster which functions to keep the kiln tube in place, besides helping to keep the kiln cylinder up and down. and maintenance of PT Indocement Tunggal Pakarsa Tok's Rotary Kiln Plan 10 as a report on practical work that has been carried out.